New observations and expansion in the distribution of Stenocercus aculeatus (Iguanidae: Tropidurinae) in southern Ecuador - Falcón-Reibán, José M.; Núñez, Darwin; Sozoranga-Farez, Johe A.; Sánchez-Nivicela, Juan Carlos (ACI Avances en Ciencias e Ingenierías, 2022)
The lizard Stenocercus aculeatus, since its description made from specimens preserved in scientific collections, its color patterns and other external aspects unknown, is a little-known species. In Ecuador it has been scarcely observed and has been reported in a locality in the extreme south. We report two new records based on chance encounters during expeditions in the forests of southeastern Ecuador and identified from detailed photographs of S. aculeatus, extending their distribution 62 km northeastern of their northern record. We also present information on their color patterns and photographs of specimens in life.